2021
DOI: 10.1088/1755-1315/686/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the feasibility of Bali cattle breeding business in Barru Regency, South Sulawesi, Indonesia

Abstract: The Indonesian Ministry of Agriculture legislates Barru Regency in South Sulawesi as a Bali cattle breeding. The purpose of this study calculates the feasibility of the Bali cattle breeding business. The research conducted in Tanete Riaja District, Barru Regency, South Sulawesi. The number of respondents is 75 farmers determined by purposive sampling. This study used survey methods and data collected by observation and interviews using a questionnaire. Primary data such as the characteristics of respondents, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Thus, the calving interval for Bali cattle was estimated at 12 months and can produce a calf every year. [7] stated that in Bali cattle breeding business, cows produces calves in the first year, and such reproductive performance allows farmers to sell calves every year.…”
Section: Gross Margin Analysis Of Breeding Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the calving interval for Bali cattle was estimated at 12 months and can produce a calf every year. [7] stated that in Bali cattle breeding business, cows produces calves in the first year, and such reproductive performance allows farmers to sell calves every year.…”
Section: Gross Margin Analysis Of Breeding Businessmentioning
confidence: 99%
“…Gross margin analysis of fattening business using Bali cattle and crossbred be better if the number of cattle is larger. [7] suggested that Bali cattle breeding business is feasible for smallholder farmer in rural area if farmers raise a minimum of 3 cattle.…”
Section: Gross Margin Analysis Of Breeding Businessmentioning
confidence: 99%
“…This is needed to achieve the highest average level of animal body weight gain during the growth period of young cattle or commercially achieved milk production (Owens et al, 2014). Bali cattle are one of the original Indonesian cattle that are widely kept by farmers and are included as a commodity for beef cattle (Baliarti et al, 2021;Kusumastuti et al, 2021). Protein is one of the nutrients that play a role in body weight gain, so this study used Bali cattle with rumen fistula.…”
Section: Introductionmentioning
confidence: 99%